Bandgap-engineered GaAsSb alloy nanowires for near-infrared photodetection at 1.31 μm. (21st September 2015) - Ma, Liang; Zhang, Xuehong; Li, Honglai; Tan, Huang; Yang, Yankun; Xu, Yadan; Hu, Wei; Zhu, Xiaoli; Zhuang, Xiujuan; Pan, Anlian
Abstract: Single-nanowire photodetectors have potential applications in integrated optoelectronic devices and systems. Here, bandgap-engineered GaAs0.26 Sb0.74 alloy nanowires were synthesized via a chemical vapor deposition method. The synthesized nanowires are single crystals grown along the [111]B direction with length up to 50 μ m and diameter ranging from 40 to 500 nm. Photodetectors are built based on these single-alloy nanowires, which show a wide response in the near-infrared region with a high response peak located in the optical communication region (1.31 μ m), as well as an external quantum efficiency of 1.62 × 10 5 %, a responsivity of 1.7 × 10 3 A W −1 and a short response time of 60 ms. These novel near-infrared photodetectors may find promising potential applications in integrated infrared photodetection, thermal imaging, information communication and processing.